Metformin in nucleus accumbens core reduces cue‐induced cocaine seeking in male and female rats. (16th March 2022) - Chan, Amy; Willard, Alexis; Mulloy, Sarah; Ibrahim, Noor; Sciaccotta, Allegra; Schonfeld, Mark; Spencer, Sade M.
Abstract: This study investigated the potential therapeutic effects of the FDA‐approved drug metformin on cue‐induced reinstatement of cocaine seeking. Metformin (dimethyl‐biguanide) is a first‐line treatment for type II diabetes that, among other mechanisms, is involved in the activation of adenosine monophosphate activated protein kinase (AMPK). Cocaine self‐administration and extinction is associated with decreased levels of phosphorylated AMPK within the nucleus accumbens core (NAcore). Previously, it was shown that increasing AMPK activity in the NAcore decreased cue‐induced reinstatement of cocaine seeking. Decreasing AMPK activity produced the opposite effect. The goal of the present study was to determine if metformin in the NAcore reduces cue‐induced cocaine seeking in adult male and female Sprague Dawley rats. Rats were trained to self‐administer cocaine followed by extinction prior to cue‐induced reinstatement trials. Metformin microinjected in the NAcore attenuated cue‐induced reinstatement in male and female rats. Importantly, metformin's effects on cocaine seeking were not due to a general depression of spontaneous locomotor activity. In female rats, metformin's effects did generalize to a reduction in cue‐induced reinstatement of sucrose seeking. These data support a potential role for metformin as a pharmacotherapy for cocaine use disorder but warrant caution given the potential for metformin's effects to generalize to a natural reward in female rats. Abstract : Metformin is a type II diabetes drug known to activate the cellular energy sensor AMPK. It has previously been shown that phopsho‐AMPK is decreased after cocaine self‐administration and extinction. Here, we report that metformin microinjected in the nucleus accumbens core reduces cue‐induced reinstatement of cocaine seeking.